SYNTHESIS AND INVESTIGATIONS OF ANIONIC LANTHANIDE COMPLEXES WITH N- N-(DIALLILAMINOPHOSPHORYL)-4- METHYLBENZENESULFONAMIDE: UDC 546.650+543.42 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
The new sulfonamidephosphate type ligand (HL=п-CH3(C6H4)SO2N(H)P(O)(N(H)CH2CH=CH2)2 ) and its sodium salt (NaL) have been synthesized. Some of lanthanide (III) coordination compounds of the general formula Na[LnL4] ( where Ln = La, Nd, Eu, Tb) have been obtained and characterized by means of 1Н NMR, IR and UV-Vis- spectroscopy. The bidentate coordination of the ligand via the oxygens of phosphoryl and sulphonyl has been concluded.
Keywords: sulfonylamidophosphates, lanthanides, coordination compounds